Case Report: Right Heart Failure Mistaken for Obesity—A Fault of Telemedicine - Sabiniewicz, Anna; Lubocka, Paulina; Sabiniewicz, Robert (Frontiers in Pediatrics, 2022)
As a result of the COVID-19 pandemic, telemedicine has become an important branch of healthcare worldwide. Apart from their undeniable advantages, the virtual visits lack physical examination, which can lead to important diagnostic mistakes. We hereby present a case of a pediatric patient whose weight gain, initially attributed to a sedentary lifestyle was, in fact, due to subacute right heart failure in the context of a ruptured sinus of Valsalva aneurysm. The condition was not diagnosed until the patient presented at the emergency. The boy was successfully treated with two percutaneous interventions and returned to his previous stature.